Energias renováveis : a terminologia da biomassa em português brasileiro e sua variação intralinguística - Pagani, Edh Carlos Soares (2017)
The technological advances have an extension of knowledge and techniques for the generation and distribution of energies. Combined with the concern to develop new sustainable forms for a national and global energy matrix, an area of specialization for renewable energies gains space in discussions and research in the globalized world. The contribution of the area of Letters in question is linked to Terminology, since it is constituted in a subarea of the sciences of the lexicon, presenting a theory and another applied. The terminology studies bring together both a description of specialized units of knowledge (UCEs or terms) and the set of methodological guidelines for the treatment of units with their terminological products, such as glossaries and dictionaries. This was a motivation to organize a corpus of textual bases in Brazilian Portuguese (PB) formed by norms, theses and dissertations referring to biomass energy, a subarea of renewable energies. As justifications for a test of this subarea of knowledge for its economic and social economy in Brazil and in the world and its terminology still not systematized. With no corpus consisting of more than 14 million occurrencewords tokens and 5 million types, 438 applications for representative terms from this subarea were selected with the help of experts, 55 of which were collected for analysis to verify that the known parameters. By literature on the topic intralinguistic variation was identified in this nomenclature presented. Starting from the theoretical and methodological principles of the Communicative Terminology Theory (TCT) and the variation with its types and causes, the results showed that the terms are presented and are presented. Be of fundamental importance to consultants and translators.